PENGARUH BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK KOSMETIK WARDAH - Vivi Putri Haryani; Dedi Mulyadi; Sungkono Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of brand equity, measured through brand awareness, brand association, perceived quality, brand loyalty, and brand attitude, both collectively and partially, on purchasing decisions of Wardah products. The study employs a quantitative method with a causal problem formulation. Data collection is conducted through questionnaire distribution. The sampling technique used is non-probability purposive sampling, focusing on consumers using Wardah products within the University Buana Perjuangan Karawang student community, with a sample size of 30 respondents. Multiple linear regression and hypothesis testing are used for data analysis. Wardah brand has become one of the leading local brands in Indonesia, known for its halal skincare products that have garnered a large following, especially among Muslim women